DOI: 10.31274/rtd-180813-17064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and analysis of traits related to improvement of popcorn

Abstract: Table 4. QTL detected for number of days to pollen shed in F 2 plants and their F 2:3 families derived from a cross of a dent maize inbred line B104 with a popcorn inbred BP3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…In our previous studies, 158 and 28 QTLs associated with nine plant traits have been detected in F 2:3 and BC 2 F 2 generations respectively, which were developed from the same cross in this study (Li et al 2007a;2008). The F 2:3 and BC 2 F 2 populations were evaluated under the same conditions, but different from this RIL population.…”
Section: Comparative Analysis Of Qtl Related To Plant Traits In the Rmentioning
confidence: 93%
See 2 more Smart Citations
“…In our previous studies, 158 and 28 QTLs associated with nine plant traits have been detected in F 2:3 and BC 2 F 2 generations respectively, which were developed from the same cross in this study (Li et al 2007a;2008). The F 2:3 and BC 2 F 2 populations were evaluated under the same conditions, but different from this RIL population.…”
Section: Comparative Analysis Of Qtl Related To Plant Traits In the Rmentioning
confidence: 93%
“…But most of the positive alleles for grain yield components and agronomic traits main came from the dent corn parent Dan232. This showed that the utility of normal dent/flint maize to improve popcorn productivity was limited by the negative effects of the exotic germplasm on popping characteristics (Dhliwayo 2008;Ziegler 2001). Therefore, it is worth concentrating further research on the favorable QTLs with the higher contribution to agronomic traits by developing near-isogenic lines (NILs) of consistent QTL and their chromosome segment substitution lines (CSSL).…”
Section: Potential Applications To Improve Agronomic Traits In Popcornmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping QTL for popping characteristics would be of benefit to conduct marker assisted selection (MAS) to overcome the shortcomings of the destructive popping test according to phenotype. Using 3 kinds of temporary genetic segregation populations derived from crosses between popcorn and dent or flint corn inbred lines, QTL for several popping characteristics have been identified on different chromosome regions of the genome, including BC 1 (Lu et al, 2003), BC 2 F 2 ) and F 2:3 (Babu et al, 2006;Dhliwayo, 2008;Li et al, 2006Li et al, , 2007. However, QTL detected for the same trait were highly inconsistent among those researches.…”
Section: Introductionmentioning
confidence: 95%
“…Due to primary selection of popping traits such as expansion volume and popability, popcorn is less optimized than other maize types in multiple agronomic traits such as pest susceptibility, stalk strength, and grain yield, and it has a relatively narrow breeding pool to integrate and improve agronomic traits (Robbins and Ashman, 1984;Sprague and Dudley, 1988;Dofing et al, 1991;Ziegler and Ashman, 1994). Previously, breeders' attempts at introducing dent corn germplasm into popcorn to improve its agronomic fitness have met with little success because of a negative correlation between expansion volume, a key popcorn quality trait, and grain yield (Brunson, 1937;Dofing et al, 1991;Ziegler and Ashman, 1994;Pereira and Amaral Júnior, 2001;Daros et al, 2002;Li et al, 2002Li et al, , 2007Li et al, , 2008Li et al, , 2009Dhliwayo, 2008). However, in 2018, Ren et al (2018) described an interpopulation breeding system between popcorn lines and dent "Quality Protein Maize" (QPM) varieties capable of increasing essential amino acid lysine in the seed proteome to more suitable levels for human dietary needs, and restored popping at early stages in the breeding program.…”
Section: Introductionmentioning
confidence: 99%